Solon the Athenian and Deioces the Mede: The Politics and Political Theory of the Ancient Arbitrator - Ober, Josiah (Classica et Mediaevalia, 2026)
The traditions concerning Deioces, King of the Medes, and Solon of Athens, preserved in Herodotus, [Aristotle] Ath. Pol., and Plutarch each concern a public arbitrator who is granted special authority through an agreement reached among rationally self-interested members of his community. In each case, the eventual outcome is the establishment of a regime in which public law enables the conditions of peaceful coexistence. Yet the differences are also stark, revealing how the Greek tradition addressed the compatibility of political liberty and social order. In each case, the agreement can be modeled as a strategic game: Deioces and the Medes play a variant of an Ultimatum Game from which Deioces emerges as absolute sovereign. By contrast, through the intermediary of Solon, rich and poor Athenians play a Bargaining Game, leaving both sides better off than they would have been through fighting, and setting the stage for collective self-government.